2017
DOI: 10.1159/000478900
|View full text |Cite
|
Sign up to set email alerts
|

The Cumulative Effects of the <b><i>MYH7</i></b>-V878A and <b><i>CACNA1C</i></b>-A1594V Mutations in a Chinese Family with Hypertrophic Cardiomyopathy

Abstract: Aims: We investigated the pathogenesis of MYH7-V878A and CACNA1C-A1594V mutations in a Chinese family with hypertrophic cardiomyopathy. Methods: Clinical, electrocardiographic (ECG), echocardiographic, and cardiac magnetic resonance (CMR) examinations of members of a Chinese family were followed by exon and boarding intron analyses of 96 genes in the proband using second-generation sequencing. We confirmed the mutations by bidirectional Sanger sequencing in the members and in 300 healthy controls. Results: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…70 Specific surface area and pore size were obtained by the Brunauer-Emmett-Teller (BET) nitrogen adsorption measurement using ASAP 2020 Surface Area and Porosity Analyzer (Micromeritics, Norcross, GA, USA). 31 The capacitance values were calculated from GCD curves 105 according to the following equations 30 half-cell: The element compositions of electrode materials as prepared were determined by an energy dispersive X-ray spectroscopy (EDS, Hitachi SU8000, Japan).…”
mentioning
confidence: 99%
“…70 Specific surface area and pore size were obtained by the Brunauer-Emmett-Teller (BET) nitrogen adsorption measurement using ASAP 2020 Surface Area and Porosity Analyzer (Micromeritics, Norcross, GA, USA). 31 The capacitance values were calculated from GCD curves 105 according to the following equations 30 half-cell: The element compositions of electrode materials as prepared were determined by an energy dispersive X-ray spectroscopy (EDS, Hitachi SU8000, Japan).…”
mentioning
confidence: 99%
“…GO terms. Calcium channel, voltage-dependent, L type, alpha 1C subunit ( CACNA1C ) gene encodes an important subunit in calcium channels, which is related to heart disease and psychosis [ 48 ]. In our study, this gene was categorized into arrhythmogenic right ventricular cardiomyopathy, calcium signalling pathway, cardiac muscle contraction, Alzheimer's disease etc.…”
Section: Resultsmentioning
confidence: 99%
“…The subjects carrying this p.V 878A mutation showed moderate or mild HCM phenotypes. 27) The p.V878L variant also has been reported by GeneDx (https://www.ncbi.nlm.nih.gov/clinvar/variation/18 1197), and the database says it is a variant of unknown significance. We found that it is a deleterious variant.…”
Section: Discussionmentioning
confidence: 99%